2022
DOI: 10.1021/acsami.1c23780
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Chemoradiotherapy of Prostate Cancer Using Gold Nanoclusters with Protease Activatable Monomethyl Auristatin E

Abstract: Combined radiotherapy (RT) and chemotherapy are prescribed to patients with advanced prostate cancer (PCa) to increase their survival; however, radiation-related side effects and systematic toxicity caused by chemotherapeutic drugs are unavoidable. To improve the precision and efficacy of concurrent RT and chemotherapy, we have developed a PCa-targeted gold nanocluster radiosensitizer conjugated with a highly potent cytotoxin, monomethyl auristatin E, PSMA-AuNC-MMAE, for RT and chemotherapy of PCa. This approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…In another report, Li and co-workers demonstrated a transformable AuNC aggregate-based synergistic strategy, which can improve the tumor retention/penetration of the nano-radiosensitizers and weaken the radio-resistance of cancer cells [ 83 ]. In a quite recent study, Burda’s group and Basilion’s group reported that when conjugating AuNCs with protease activatable monomethyl auristatin E, the specificity and efficacy of radiation and chemotherapy can be significantly improved [ 84 ]. Both in vitro and in vivo results showed selective tumor cell uptake, excellent anti-tumor activity, and prolonged chemotherapeutic effect [ 84 ].…”
Section: Gold Nanostructures For Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In another report, Li and co-workers demonstrated a transformable AuNC aggregate-based synergistic strategy, which can improve the tumor retention/penetration of the nano-radiosensitizers and weaken the radio-resistance of cancer cells [ 83 ]. In a quite recent study, Burda’s group and Basilion’s group reported that when conjugating AuNCs with protease activatable monomethyl auristatin E, the specificity and efficacy of radiation and chemotherapy can be significantly improved [ 84 ]. Both in vitro and in vivo results showed selective tumor cell uptake, excellent anti-tumor activity, and prolonged chemotherapeutic effect [ 84 ].…”
Section: Gold Nanostructures For Cancer Treatmentmentioning
confidence: 99%
“…In a quite recent study, Burda’s group and Basilion’s group reported that when conjugating AuNCs with protease activatable monomethyl auristatin E, the specificity and efficacy of radiation and chemotherapy can be significantly improved [ 84 ]. Both in vitro and in vivo results showed selective tumor cell uptake, excellent anti-tumor activity, and prolonged chemotherapeutic effect [ 84 ].…”
Section: Gold Nanostructures For Cancer Treatmentmentioning
confidence: 99%
“…Although it is out of the scope of the present review, it is important to mention alternative tactics that are being explored with the auristatins with the objective of targeting cancer cells in a highly selective manner by means of platforms different from antibodies recognized by tumor antigens. Among these alternative devices, it is worth highlighting low-molecular-weight ligands for antigens such as the prostate-specific membrane antigen (PSMA) [ 129 ] or integrin ανβ 3 [ 130 ], aptamers [ 131 ], gold nanoclusters [ 132 ] or radiolabeled proteins [ 133 ].…”
Section: Chemistry and Biology Of Marine Antibody-drug Conjugatesmentioning
confidence: 99%
“…Major challenges in achieving effective GBM therapy responses are tumor-specific drug delivery and off-target side effects. Preclinical and clinical studies have investigated potent tubulin polymerization inhibitors from the monomethyl auristatin family conjugated to antibodies (known as antibody-drug conjugates or ADCs) as potential treatments for a wide variety of cancers including GBM 5 , 6 , 22 . This ADC approach can successfully deliver cytotoxic drugs but often leads to inadequate retention in tumors due to substantial intertumoral and intratumoral variation in antibody accumulation 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in a GBM U87ΔEGFR-luc xenograft model, the heterogeneous drug/antibody ratio failed to reach a satisfying therapeutic outcome 14 , 25 . As an alternative to antibodies, researchers have developed nanoparticles with reductive-sensitive linkers or prostate-specific membrane antigen (PSMA)-targeting plus cathepsin B (Cat B)-activatable linkers to deliver tubulin inhibitors to tumors 5 , 7 .…”
Section: Introductionmentioning
confidence: 99%